answer: i cant see the graphs but i can you find the answer
the first point we'll be 0,0 and then you go up the y axis 4 places and over to the right 1 so your second point will be 1,4
f(x) = 4^(x-1) + 2
f(4) = 4^(4-1) + 2
= 4³ + 2 = 66
f(2) = 4^(2-1) + 2
= 4¹ + 2 = 6
Average rate of change:
(66 - 6)/(4 - 2)
Option B is correct.
Average rate of change from x=1 to x=2 is 3
Formula for Average rate of change: The ratio of the difference in the function f(x) as it changes from a to b to the difference between a and b :
As per the statement:
Calculate the average rate of change from x =1 to x =2
At x = 1
At x = 2
Therefore, the average rate of change from x=1 to x=2 is 3
The answer to this is (1,4) Hope this helps you guys.
We know that the given function f(x) is a exponential function .
Also, the graph of the function f(x) is a exponential growth with scale factor 4.
Since, the each term is 4 times it's preceding term.
and the end behavior of the function is:
as x→ -∞ then f(x)→ 0
( Since, )
as x → ∞ then f(x) → ∞
Also, the graph of the function f(x) could be seen with the help of a graph attached to it.
I really hope this answer helps you out! It makes my day helping people like you and giving back to the community that has helped me through school! If you could do me a favor, if this helped you and this is the very best answer and you understand that all of my answers are legit and top notch. Please mark as brainliest! Thanks and have a awesome day!
f(x) = 4^(x-1) +2
the average rate of change on the interval [1, 2] is found by computing
(f(2) - f(1))/(2 - 1)
= ((4^1+2) - (4^0+2)/1
So if you take x=0, you get y=0; which is the origin.
And when x=1, y=4.
You should get something like the attached picture.